Learning Linux Shell Scripting: Leverage the Power of Shell Scripts to Solve Real-World Problems - Naik, Ganesh Sanjiv (Packt Publishing, Limited, 2018)
Linux has been one of the widely adopted and popular OS when it comes to leveraging scripting and automating common tasks. With this book, readers will get to grips with shell scripting, automating repetitive tasks, text processing, regular expressions, pattern matching, backup and restore, and much more. The end goal of this book is to get.